TGF‐β triggers HBV cccDNA degradation through AID‐dependent deamination. Issue 3 (2nd February 2016) - Qiao, Ying; Han, Xiaoxu; Guan, Gefei; Wu, Na; Sun, Jianbo; Pak, Vladimir; Liang, Guoxin
Abstract : The covalently closed circular DNA (cccDNA) of hepatitis B virus (HBV) is a viral center molecule for HBV infection and persistence. However, the cellular restriction factors of HBV cccDNA are not well understood. Here, we show that TGF‐β can induce nuclear viral cccDNA degradation and hypermutation via activation‐induced cytidine deaminase (AID) deamination activity in hepatocytes. This suppression by TGF‐β is abrogated when AID or the activity of uracil‐DNA glycosylase (UNG) is absent, which indicates that AID deamination and the UNG‐mediated excision of uracil act in concert to degrade viral cccDNA. Moreover, the HBV core protein promotes the interaction between AID and viral cccDNA. Overall, our results indicate a novel molecular mechanism that allows cytokine TGF‐β to restrict viral nuclear cccDNA in innate immunity, thereby suggesting a novel method for potentially eliminating cccDNA. Abstract :